Civil-Military Cooperation (CIMIC) in Humanitarian Assistance and Disaster Relief (HADR): The Legal Frameworks - Chaisorn, Panita (Faculty of Law, Universitas Brawijaya, 2022)
Civil-military cooperation (CIMIC) is one of the most crucial factors for a successful humanitarian assistance and disaster relief (HADR) operation. It is important to foster the relationship between these two sectors to pursue effective outcomes for the operation. Therefore, a developed mechanism for civilian-military coordination including clear CIMIC frameworks is needed. This paper explores the frameworks/guidelines on CIMIC in HADR issued by three international organizations, namely the United Nations (UN), the North Atlantic Treaty Organization (NATO), and the Association of Southeast Asian Nations (ASEAN). The focus of this study will be on the operation at the operational phase. The CIMIC fundamentals and principles of the foreign military sector will be scrutinized. Consequently, the analysis would help identify the essential subjects for policymakers to consider and issue the proper national framework for CIMIC in HADR.